Gender Dynamics of Poverty Coping Strategies Among Farming Households in Akoko South-West Ondo State, Nigeria - Stephen, Ojo Olutope; M.A., Abdulaleem; S.F., Ajidahun (Pancasila International Journal of Applied Social Science, 2026)
This study examines gender-based differences in poverty coping strategies among rural farming households in Akoko South Local Government Area, Ondo State, Nigeria. A multi-stage sampling technique was used to select 120 respondents, comprising equal numbers of male- and female-headed households from six randomly chosen communities. Primary data were collected through structured questionnaires and analyzed using descriptive statistics, the Foster–Greer–Thorbecke (FGT) poverty index, and logistic regression models. Findings reveal significant gender disparities in household characteristics, economic activities, and poverty levels. The average age of female-headed households was 44.7 years, compared to 53.4 years for male-headed households. Educational attainment was relatively high, with 56.7% of female and 46.6% of male household heads having tertiary education. Male-headed households recorded higher average incomes (₦56,664,100) and a lower poverty incidence (30%) than female-headed households (53.4%). The FGT index further indicated a greater poverty depth among female-headed households (0.534). Livelihood activities differed, with 70% of male-headed households engaged in farm labour and an equal proportion of female-headed households involved in the sale of agricultural products. Logistic regression identified marital status, income level, and participation in crop processing as significant determinants of poverty status. Reducing the number of daily meals was the most common coping strategy. The study highlights the need for gender-responsive rural development policies that promote equitable access to credit, productive resources, and training. Targeted empowerment programmes for female-headed households can strengthen resilience and support sustainable poverty reduction in rural communities.